ANTI-FREEZING ADHESIVE EXPERIMENTAL STUDY BASED ON BIONICS - WANG ChunHua; XU HanWen; WANG ZhongXian; QU Hui (Jixie qiangdu)
In order to solve the freezing adhesive problem on roller and belt during coal transportation process in winter,on the basis of referring to relevant freezing adhesive theory,inspired by bionics,we did the theoretical analysis and experimental research about the application of bionic convex hull geometry structure on the roller and belt. In theory,it is verified bionic convex hull geometry structure can increase the the water contact angle,to a certain extent,it can reduce the freezing adhesive strength. We referred to the existing anti-freezing adhesive experimental study,used the UHMW-PE,designed and processed a bionic convex hull template,the height is 1. 0 mm,projected radius is 1. 0 mm,the center distance is 6. 4 mm,and another same material smooth template,by homemade freezing adhesive strength test device,under conditions of-25℃ temperature and3 h freezing time,we tested the freezing adhesive characteristics of two kinds of templates with moisture content 40% of the coal slime. The results showed that the normal freezing adhesive strength and tangential freezing adhesive strength of bionic convex hull template reduced about 8% and 12% respectively,we verified the bionic geometric convex hull indeed had certain antifreezing ability from the experiment aspect,hope can be used in anti-freezing adhesive field.